The role of adverse economic environment and human capital on collaboration within agri-food supply chains. (June 2020) - Papaioannou, Grammatoula; Mohammed, Anne-Marie; Despoudi, Stella; Saridakis, George; Papadopoulos, Thanos
Highlights: Discusses collaboration within agri-food supply chains. Explains how adverse economic conditions impact on agri-food supply chains. Explains how human capital impacts on agri-food supply chains. Reveals that under adverse economic conditions, the farmers do not collaborate. Abstract: This paper examines the role of adverse economic conditions and human capital on different types of collaboration within agri-food supply chains. Data was collected from the Greek agricultural sector, covering periods of economic hardship. The results reveal that the impact of adverse economic conditions on the collaborative constructs of goal congruence, decision synchronization, incentive alignment, resource sharing and joint knowledge creation is nonlinear, specifically an inverted U for all of them. For collaboration constructs of information sharing and collaborative communication, the results reveal that under adverse economic conditions, the farmers do not collaborate. We also show that aspects of human capital such as age, education and farming experience affect collaboration. Our contribution lies in investigating the potential non-linear relationship between adverse economic conditions and various types of collaboration. Therefore, this study provides several managerial implications and insight for policymakers, while filling a crucial gap in the literature due to the limited existing studies that consider the impact of adverse economic conditions on agri-food supply chains.